The Influence of Online Customer Reviews and Online Customer Ratings on Product Purchase Decisions on The Tokopedia Marketplace - Yanti, Desma; Ningsih, Nonita Kristya; Ony, Johan Gunady; Suhalim, Shinta Putri (Universitas Pamulang, 2024)
The purpose of this study is to find out the influence of online customer reviews and online customer ratings on purchasing decisions. The target of this study is Indonesian people who have shopped using Tokopedia. The method to be used in this study is a survey method by distributing questionnaires online as a data collection tool. The sample to be used in this study is 100 respondents randomly selected from Indonesian people who have shopped at Tokopedia. The collected data will be analyzed using linear regression methods to test the hypotheses that have been formulated.